Pengaruh Social Media Marketing dan Store Atmosphere Terhadap Keputusan Pembelian Pada Kafe Janji Jiwa Muara Bungo - Primaraja, M. Fadjrin; Yuniarti, Yenny (Magister Manajemen Universitas Wisnuwardhana, 2026)
This study aims to analyse the influence of social media marketing and store atmosphere on purchasing decisions at Janji Jiwa Muaro Bungo café. This study uses quantitative analysis and a descriptive approach. The data sources used in this study are data from questionnaires filled out by 100 consumers, interviews and observations. In the initial stage, data quality tests were conducted, namely validity and reliability tests. The results of these tests showed that the data was valid and reliable. The results of the analysis were as follows: first, social media marketing did not have a significant effect on purchasing decisions. Second, store atmosphere had a significant effect on purchasing decisions. Third, social media marketing and store atmosphere simultaneously had a significant effect on purchasing decisions.